Penerapan Model Pembelajaran Kooperatif Tipe Make a Match Untuk Meningkatkan Keaktifan dan Hasil Belajar Peserta Didik SDN 171 Rejang Lebong - R.A. Tri Marchieta Artamulia Aminy; Herman Lusa; Nani Yuliantini (Universitas Bengkulu, 2021)
AbstractThis study aims to describe steps of make a match model, to improve activeness and learning outcomes of grade III students at SDN 171 by applying a Make a match model. The subjects of this study were teachers and students. Data collection techniques in the form of observations and tests. Assessment instruments in the form of observations and tests. Observation data analysis techniques use the formula of average score, highest score, lowest score, score difference and range values for each criterion. The test data is analyzed using the formula of average grades and classical percentages. The results of the teacher activity research in the application of model Make a match cycle I obtained a score of 61.15 (good) and cycle II increased by 80.15 (very good), the activeness of learning learners in cycle I obtained a score of 10.05 (sufficient) and increased in cycle II obtained an average score of 13.12 (good). The results of learning cycle I in Indonesian subjects in classroom amounted to 67.48 with classical completion of 47.05%, in cycle II average grade value was 75.74 with classical completion of 76.47%. Mathematics subjects in cycle I obtained an average class of 69.55 with classical completion of 70.58%, in cycle II the average grade score of 81.13 with classical completion of 88.23%. Thus, it can be concluded that the application of Make a match model can improve the activeness and learning outcomes of students in Grade III SDN 171.Keywords: Make a match, Liveliness, Learning Outcomes.